End of empire policies, and the politics of local elites: the British exit from south Arabia and the Gulf, 1951-1972. - Sammut, D (2014)
The unusual way in which Britain's empire in Arabia was connected politically and constitutionally to the metropole, and the perceived – in some instances exaggerated – view of its strategic and economic importance, created both an opportunity and a justification for the British disengagement from the region to happen differently than in most of the rest of the empire. Strong personalities – in the metropole, amongst the men on the spot, and among local elites – played a crucial role in decision-making, and this thesis argues that informal networks from among these three constituencies worked in parallel to the established formal channels, impacting policy and driving the decision-making process. These networks initially contributed to a break in the political consensus within the metropole, but eventually also helped to restore it. The manipulation of local elites was the tool of choice, used by Britain (under both Conservative and Labour Governments) and its "men on the spot", in their endeavour to secure a lasting privileged position in Arabia. How key actors adapted to change, both in their own societies and in the international system, often determined the success or otherwise of their endeavours. This tangled tale of Britain’s last imperial stand in Arabia is far from being a unique case of how modern empires have handled unusual episodes of imperial retreat. The story has echoes in two other imperial exits of the late 20th century – the French disengagement from Algeria from 1954 to 1962, and Russian efforts to maintain a privileged position in Georgia, immediately before and after the collapse of the USSR in 1991, and since. Even if it is too early to draw firm conclusions, similar patterns – as the ones discussed in this thesis with regards to the end of the British Empire in Arabia – can also be observed in the other two cases, allowing us to draw some observations and lessons.